WITHDRAWN: Design and Implementation of an Open-Source Security Operations Center for Effective Cyber Threat Detection and Response - Rakesh Bhavsar; Vishvjit Thakar (2025)
Abstract 26 June, 2025. Research Square has withdrawn this preprint due to overlap with another author's [published work](https://doi.org/10.9734/jerr/2024/v26i71203).